2010
DOI: 10.1682/jrrd.2009.09.0152
|View full text |Cite
|
Sign up to set email alerts
|

An indentation apparatus for evaluating discomfort and pain thresholds in conjunction with mechanical properties of foot tissue in vivo

Abstract: Abstract-The mechanical properties of human foot tissue in vivo as well as discomfort and pain thresholds are important for various applications. In this study, an apparatus for measuring the discomfort and pain thresholds and the mechanical properties of human tissues is presented. The apparatus employs a stepper motor that controls the indentation speed, as well as a load cell and potentiometer that determine the corresponding reaction force and tissue deformation (displacement), respectively. A LabVIEW prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 38 publications
0
38
1
Order By: Relevance
“…However, previous studies reported a PPT of about 1100 kPa at the heel of young Chinese adults (Rodrigo et al, 2013;Xiong et al, 2010). Again, such a difference may be a reflection of the higher thresholds in the population tested.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…However, previous studies reported a PPT of about 1100 kPa at the heel of young Chinese adults (Rodrigo et al, 2013;Xiong et al, 2010). Again, such a difference may be a reflection of the higher thresholds in the population tested.…”
Section: Discussionmentioning
confidence: 65%
“…Even though we evaluated the thresholds at 95 points, the clustering indicates that testing five points can reveal the behavior of the plantar foot surface due to similarities across locations. Thus, the points chosen by Rodrigo et al, (2013) and Xiong et al, (2010) are justified.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations